A house next door to trauma : learning from Holocaust survivors how to respond to atrocity - Hassan, Judith, 1946- (Jessica Kingsley Publishers, 2003)
Drawing on her long-standing experience as a manager of services for refugees and survivors, Judith Hassan presents a practical guide to working with people who have lived through war trauma. She explores the particular challenges caring professionals face in supporting this group, and develops a working model that takes into account the therapist's own response to the trauma and how this impacts on the therapeutic relationship. Specific issues covered include: issues of loss, grief and mourning in relation to trauma; the role of the social, political and cultural context of the trauma; the ef.